A lei de incentivo ao esporte do Governo Federal: um olhar sobre os proponentes e seus desafios nas etapas de aprovação do projeto - Marcus Peixoto de Oliveira (2020)
The Federal Sports Incentive Law (SIL), the object of this research, represents one relevant tool of public funding to sports projects. Established by the Law nº 11.438/06, it is active for approximately 13 years as a mechanism that includes private and public actors, ratifying a tendency on public policies implementation, mainly social. The current study focuses on proposing institutions which present projects to the Special Secretariat of Sports aiming to obtain financial resources via tax deduction in the execution of their activities. So, the global aim is to comprehend the challenges imposed and perceived by these proponents over the approval steps on the sports projects proposals. Therefore, consisting of an analysis of public policies implementation, it reflects on the level of state intervention, the financial model, on the profile of the implementing actors and the legal framework that offers the guidelines to follow. To reach the intended goals, it resorted to the political science field and academic papers which owned a direct connection to sports public policies. After, it was necessary a documental investigation which analysed official documents related to the central theme of the study as: federal agencies control reports; laws, decrees, acts; and administration statements of the SIL containing numbers to help its understanding. In parallel, it uses semistructured interviews as primary fonts, made with eight representing managers of proposing institutions participants of the enrollment process and project final approval. This perspective frames the study as social research which displays a qualitative approach complemented by quantitative data. Hence, considering the analysis, stands out: the State venture on this kind of social public policy; reinforces the Third Sector as the principal operator responsible for the execution of activities; and changes on the SIL directives, particularly over the last years, impacting the relations between the proposing institutions and this mechanism, implying necessary shifts on the profile of the submitted projects. As well as the crucial overcoming of historical challenges, like, regional concentration, procedural promptness and efficient communication.